2010
DOI: 10.1007/s11060-010-0283-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aberrant p53 function on temozolomide sensitivity of glioma cell lines and brain tumor initiating cells from glioblastoma

Abstract: The most effective chemotherapeutic for glioblastoma (GBM) is the DNA alkylating agent temozolomide (TMZ). In a recent study by Hegi et al. benefit from TMZ was significantly associated with methylation of the promoter of the O6-methylguanine-DNA methyltransferase (MGMT) gene; however, the correlation was imperfect. Some patients with methylated tumors were short survivors and others with unmethylated tumors were long survivors. These exceptions have raised the possibility that TMZ response might be influenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 18 publications
3
70
0
Order By: Relevance
“…19 Mutant p53 has been shown to induce radiochemotherapy resistance in many cancer types including GBM, 24 with altered p53 expression resulting in increased sensitivity to temozolomide in one experimental model. 3 Reasons for the lack of a clear correlation of p53 with prognosis are many-fold, including the complexity of the p53 signaling pathway, the importance of other regulators in the p53 pathway that may be altered in GBM (for example, Rb, MDM2), and the heterogeneity of p53 mutation types and effects. 12 In fact, methods to target p53 in clinical trials have also been limited by these issues.…”
Section: 32mentioning
confidence: 99%
“…19 Mutant p53 has been shown to induce radiochemotherapy resistance in many cancer types including GBM, 24 with altered p53 expression resulting in increased sensitivity to temozolomide in one experimental model. 3 Reasons for the lack of a clear correlation of p53 with prognosis are many-fold, including the complexity of the p53 signaling pathway, the importance of other regulators in the p53 pathway that may be altered in GBM (for example, Rb, MDM2), and the heterogeneity of p53 mutation types and effects. 12 In fact, methods to target p53 in clinical trials have also been limited by these issues.…”
Section: 32mentioning
confidence: 99%
“…The role of p53 in temozolomide resistance is far from being understood. Although several groups reported that p53 status is not predictive of response to chemotherapy with alkylating agents (18,21), more recent works suggest that the absence of a functional p53 increases temozolomide sensitivity in glioma cell lines (22) and in intracranial glioblastoma xenografts (23). A trend toward an increased temozolomide sensitivity in patients with p53 mutations was also suggested (24).…”
Section: Discussionmentioning
confidence: 99%
“…Blough et al delineated that traditional glioma cell lines that did not express a functional p53 were significantly more sensitive to TMZ than cell lines with functionally intact wild-type p53 expression. RNAi specific for p53 had little effect on sensitivity in p53 null glioma cells (21). Thus, we examined whether low expression of miR-221/222 can sensitize the effects of TMZ in different p53 status glioma cells.…”
Section: Discussionmentioning
confidence: 99%